Dual-Wavelength Passively Q-Switched Erbium-Doped Fiber Laser Incorporating Calcium Carbonate Nanoparticles as Saturable Absorber - Iman N. Jasem; Hiba H. Abdullah; Mohammed Jalal Abdulrazzaq (Journal of Nanotechnology)
This study experimentally demonstrates the operation of a dual-wavelength passively Q-switched erbium-doped fiber laser that incorporates CaCO3 nanoparticles as a saturable absorber (SA). The SA was prepared by using the drop-casting method, wherein CaCO3 nanoparticles were embedded in a polyvinyl alcohol (PVA) polymer to form a CaCO3/PVA film SA. The film was integrated into a ring laser cavity with a 976 nm pump to generate Q-switched pulses. The properties of the SA were examined experimentally, and its modulation depth is approximately 47%. As the pump power increased from 180 mW to 270 mW and the pulse repetition rate increased from 12.67 kHz to 21.3 kHz, the corresponding pulse width decreased from 35.27 μs to 18.74 μs. The signal-to-noise ratio was approximately 25 dB, highlighting the laser’s stability. The results indicate that the proposed CaCO3/PVA SA is suitable for realizing portable Q-switched lasers.